Super-Precise Scale Bar for Reflection-Type THz Imaging - Senfeng Lai; Yanghui Wu; Jiayi Zhu; Wen Wu; Wenhua Gu (IEEE Photonics Journal)
The reflection of terahertz wave from a metallic surface with subwavelength periodic structure was investigated experimentally and theoretically. It is shown that the spatial resolution of the reflection image can be increased drastically due to excitation of spoof surface plasmon polaritons. Theoretic analysis as well as experiment comparison with nonmetallic periodic structure verified this phenomenon. Based on this study, a super-precise scale bar is proposed to improve the location and measurement precision of THz imaging, which can improve the precision by one order of magnitude.